A bistable electrochromic device based on poly(viologen)s. (February 2023) - Zhang, Yuewei; Jin, Xuchao; Zhang, Weiran; Gu, Chang; Liu, Xuesong; Zhang, Yu-Mo
Abstract: A bistable electrochromic device based on poly(viologen)s is demonstrated with good overall performance, including bistability (4981 s), switch-on voltage (−1.0 V) and reversibility (≥1000 cycles). Overall, these results imply that the control of the diffusivity of viologens is an effective methodology for achieving excellent bistability and low energy consumption. Graphical abstract: Image 1 Highlights: ECDs were fabricated from poly(viologen)s and poly(ferrocene). The ECD shows good bistable property of 4981 s. The multi-color device was achieved by mono-layered pixelated-device.